2002
DOI: 10.1046/j.1365-313x.2002.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme termination of RNA transcripts down‐regulate seed fatty acid genes in transgenic soybean

Abstract: SummaryWe investigated whether termination of transcripts with a self-cleaving ribozyme can enhance nuclear retention and serve as a tool to decrease speci®c plant gene expression. Nuclear retention was ®rst monitored in tobacco using the b-glucuronidase gene terminated with either the 35S CaMV 3¢ untranslated sequence (UTR) or a cis-acting ribozyme. Northern blot analysis of nuclear RNA and total RNA, and in situ hybridizations showed that the ribozyme-terminated transcripts were preferentially retained in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 37 publications
(39 reference statements)
2
149
1
2
Order By: Relevance
“…This can also be achieved by manipulation of TAG biosynthesis. In soybean, reduced levels of the saturated fatty acid palmitate were obtained by downreglation of FATB, an acyl-ACP thioesterase, causing the accumulation of oleic acid up to 85% from 18% in the wild type [30]. A Jatropha cDNA encoding a putative FATB homolog, JcFATB1, has been recently cloned [31].…”
Section: Targeting Plant Oil Metabolismmentioning
confidence: 99%
“…This can also be achieved by manipulation of TAG biosynthesis. In soybean, reduced levels of the saturated fatty acid palmitate were obtained by downreglation of FATB, an acyl-ACP thioesterase, causing the accumulation of oleic acid up to 85% from 18% in the wild type [30]. A Jatropha cDNA encoding a putative FATB homolog, JcFATB1, has been recently cloned [31].…”
Section: Targeting Plant Oil Metabolismmentioning
confidence: 99%
“…The nature of the postulated aberrant RNA remains unknown [1,2,5,38], but PTGS can be induced in soybean and tobacco by transgenes expressing ribozyme-truncated transcripts that are not polyadenylated and are preferentially retained in the nucleus [46]. In Drosophila, the post-transcriptional silencing of alcohol dehydrogenase transgenes-a phenomenon that is similar to PTGS induced by sense transgenes in plants-is dependent on the Argonaute family member Piwi [47].…”
Section: Potential Amplification Processes In Rnai and Ptgsmentioning
confidence: 99%
“…In the case of FATB, a previous antisense and overexpression study in Arabidopsis demonstrated that this enzyme is involved, at least in part, in the in vivo production of saturates in flowers and seeds (Doermann et al, 2000). Similarly, downregulation of FATB expression in soybean also demonstrates partial reduction of seed palmitic acid (Wilson et al, 2001;Buhr et al, 2002). However, the origin of palmitic acid, which remains after gene-silencing procedures, and the extent to which each class of thioesterase contributes in vivo to the production of exportable fatty acids by different tissues remain unresolved.…”
Section: Introductionmentioning
confidence: 98%